CA 15-3 as an alternative marker for KL-6 in fibrotic lung diseases - Kruit, A.; Gerritsen, W.B.M.; Pot, et al., N. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2010)
Background: KL-6 is a mucin that is increased in interstitial lung diseases (ILD), and in some malignancies. CA 15-3, a tumor marker for breast cancer, refers to the same mucin but utilizes antibodies against different epitopes. Objective: The aim of our study was to evaluate CA 15-3 as a viable alternative to KL-6 as a marker for ILDs with and without fibrosis. Design: Serum from 242 patients with ILDs and from 327 healthy controls were included and KL-6 and CA 15-3 were measured in all subjects. Regression analyses and ROC curves were used to compare the performances of both markers. Results: KL-6 and CA 15-3 levels were both significantly higher in the ILD patients compared to the controls (p < 0.0001). A weak yet significant correlation was found between serum KL-6 and CA 15-3 levels in the controls (R=0.39, p